2007
DOI: 10.1158/1535-7163.mct-06-0620
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapeutics for multiple myeloma: The arrival of a risk-stratified approach

Abstract: Multiple myeloma (MM) remains an incurable hematologic malignancy characterized by frequent early responses, inevitably followed by treatment relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…22 The majority of the patients with t(4;14) have an estimated median survival after diagnosis of 18-36 months despite tandem HDT, and among this population new innovative approaches are clearly needed. 21 On the contrary, and that is the major finding of this study, we have identified a subgroup of approximately 45% of the patients with both b 2 -microglobulin o4 mg/l and Hb level X10 g/dl at diagnosis which is experiencing prolonged survival after tandem transplant and benefits from HDT. The median EFS in this subgroup of patients was 27 months, strictly identical to the EFS observed in the intensive arm (single ASCT) of the French IFM90 trial, 23 of the British MRC VII trial 24 or the Italian MMSG97 trial.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…22 The majority of the patients with t(4;14) have an estimated median survival after diagnosis of 18-36 months despite tandem HDT, and among this population new innovative approaches are clearly needed. 21 On the contrary, and that is the major finding of this study, we have identified a subgroup of approximately 45% of the patients with both b 2 -microglobulin o4 mg/l and Hb level X10 g/dl at diagnosis which is experiencing prolonged survival after tandem transplant and benefits from HDT. The median EFS in this subgroup of patients was 27 months, strictly identical to the EFS observed in the intensive arm (single ASCT) of the French IFM90 trial, 23 of the British MRC VII trial 24 or the Italian MMSG97 trial.…”
Section: Discussionmentioning
confidence: 58%
“…[11][12][13][14][15]20 Some authors even suggest that these patients receive minimal benefit from ASCT and could be candidates for novel therapeutic approaches. 12,13,21 Our study, the largest one for patients with t(4;14) treated with upfront HDT, allows several comments. The overall response Heterogeneity of t(4;14) in multiple myeloma P Moreau et al rates after both induction and HDT were identical in this subgroup of patients to those achieved in patients without t (4;14) indicating that primary drug resistance may not be the main cause of disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of thalidomide and bortezomib has improved response rates and response duration in MM patients [13][14][15][16][17][18][19][20]. High-dose chemotherapy with stem cell transplantation can enhance the rate of complete remission and prolong the survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 MM is incurable with current therapies and potential therapeutic targets for new drug development is clinically important. 3 We and others have shown that mutations/deletions of p53, a tumor suppressor protein, are relatively rare in MM.…”
Section: Introductionmentioning
confidence: 99%